2017
DOI: 10.1371/journal.pone.0182624
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bactericidal and anti-biofilm properties of a novel surface-active organosilane biocide against healthcare associated pathogens and Pseudomonas aeruginosa biolfilm

Abstract: Healthcare acquired infections (HAI) pose a great threat in hospital settings and environmental contamination can be attributed to the spread of these. De-contamination and, significantly, prevention of re-contamination of the environment could help in preventing/reducing this threat. Goldshield (GS5) is a novel organosilane biocide marketed as a single application product with residual biocidal activity. We tested the hypothesis that GS5 could provide longer-term residual antimicrobial activity than existing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…It was tested against MR S. aureus ATCC 33951 and MDR P. aeruginosa ATCC BAA-2114. These bacteria are known as biofilm formers 57,58. The MBEC values were two-fold and six-fold higher than the MIC values against the planktonic form of the aforementioned bacterial strains, respectively (Table 4).…”
Section: Discussionmentioning
confidence: 98%
“…It was tested against MR S. aureus ATCC 33951 and MDR P. aeruginosa ATCC BAA-2114. These bacteria are known as biofilm formers 57,58. The MBEC values were two-fold and six-fold higher than the MIC values against the planktonic form of the aforementioned bacterial strains, respectively (Table 4).…”
Section: Discussionmentioning
confidence: 98%
“…What is clear is that the novel filamentous fungal isolate described here is a strong biofilm former; additionally, this study highlights the importance of testing antimicrobial surfaces with microbes other than the classic bacterial biofilm formers, Pseudomonas aeruginosa and Staphylococcus aureus. The antimicrobial compound used in this study was selected because it demonstrated substantial biocidal activity against both of these classic bacterial biofilm formers [25]; however, our study here indicates that when filamentous fungus is grown in the presence of the coating, the biofilm is actually larger (Figure 2). The reason for this enlarged biofilm on the coated surfaces as compared to the uncoated surfaces is not known, and further testing with microorganisms under different growth conditions could help to explain this finding.…”
Section: Metabolomic Profiling Of P Torokii Fjii-l10-sw-p1 Strainmentioning
confidence: 91%
“…Commercially available and patented organosilane, a surface-penetrating compound, was used as an antimicrobial coating on the tested surfaces. The active ingredient in the antimicrobial compound tested is 3-(trihydroxysilyl) propyldimethyloctadecyl ammonium chloride and previously assessed to control bacterial biofilm formation [25]. In the presence of hydroxyl groups at the surface of the glass, minerals, or metals (e.g., aluminum, steel), silanols formed a stable Si bond.…”
Section: Biofilm Formationmentioning
confidence: 99%
“…The technology is currently registered with the US Environmental Protection Agency (85556–1 and 85556–2). Previous work has demonstrated that Goldshield products have bactericidal properties [ [23] , [24] , [25] ]. For example, Goldshield 5 used as a coating on masks had been shown to be an effective antibacterial agent against both gram-positive and gram-negative bacteria [ 26 ].…”
Section: Methodsmentioning
confidence: 99%